การปรับปรุงมาตรฐานการตรวจสอบคุณภาพในการผลิตสีผง - ภานุเทพ อธิปัญญาพันธุ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The objective of this research was to improve the standard of surface quality inspection in powder coating products which had 3 types of surface defects: haziness, sparkle and contamination of color. There were 4 main steps of the research procedures. The first step, the main causes that effected to the inspection capability of these employees were investigated by fish bone diagram. The second step, the operators had determined the surface quality of the sample sheet before improvement to verify the main causes. The third step , the guidelines to improve the operators’ capability were proposed and applied in order to set the surface inspection standard. Finally, the fourth step, the operators had determined the surface quality of the sample sheet after improvement. The results of this research showed that the causes of the low precision and accuracy came from the operators failed to make the decisions for quality, the improper reference standard color sheets for inspection, the acceptance criteria and no standardizations. Before improvement, the percentages of attribute score were 62.50%-79.17% and the percentages of attribute screen effect score were 41.67%-66.67%. These scores were less than the acceptable value of 80%. The guidelines for the operators’ capability improvement were the followings: 1) building the standard inspection procedures, 2) providing the training course about the procedures, 3) controlling and maintaining the reference standard color sheets, and 4) clearing the meaning of the acceptance criteria. After improvement, the percentages of attribute score were 83.33-100.00% and the percentages of attribute screen effect score were 83.33%-95.83%, which were acceptable.